Gas Imports From Russia Cannot be Compensated in the Short Term - Andreas Fischer; Malte Küper; Thilo Schaefer (Wirtschaftsdienst)
Abstract As Russia’s invasion of Ukraine continues, more and more people are calling for a ban on Russian energy imports. The proponents argue that abstaining from importing billions worth of coal, oil and gas will further increase the pressure on the Kremlin. Critics, however, including German Chancellor Olaf Scholz, warn of what they believe to be incalculable consequences, with the gas supply being particularly at risk. This article outlines the different options for substituting Russian coal, oil, and especially gas and explains why the wait-and-see attitude of the German government towards a complete import ban is understandable.